Prefrontal cortex oxygenation and autonomic nervous system activity under transcutaneous auricular vagus nerve stimulation in adolescents - Höper, Saskia; Kaess, Michael; Koenig, Julian (Autonomic neuroscience, 2022)
Introduction - The Neurovisceral Integration Model (NIM) proposes a complex interplay of visceral and neural structures that are crucial for adaptive responses to environmental demands. The aim of the present study was to investigate this circuitry using experimental manipulation via transcutaneous auricular vagus nerve stimulation (tVNS), measures of peripheral autonomic nervous system (ANS) activity and prefrontal cortex (PFC) oxygenation, quantified using functional near-infrared spectroscopy (fNIRS). - Methods - In a sample of n = 30 adolescents (age 14-17 years), tVNS versus sham stimulation was applied each during a 15-minute stimulation phase in a within-subject-cross-randomized-design. Mean oxygenation of the PFC and functional connectivity were assessed using fNIRS. Additionally, heart rate variability (HRV), heart rate (HR), electrodermal activity (EDA), and saliva alpha-amylase (sAA) were assessed to quantify peripheral ANS activity. - Results - Using linear mixed-effects models, HRV increased (p < .0001) and HR (p < .0001) decreased during tVNS compared to sham. No effect on EDA or sAA was observed. PFC oxygenation increased over time under tVNS compared to sham (p = .017). The relative increase in HRV and decrease in HR was associated with increased oxygenation of the PFC (HR: p < .0001; HRV: p = .007). Exploratory analyses illustrated, that under tVNS, PFC connectivity increased compared to sham. - Conclusion - The present study supports the NIM by showing that tVNS influences ANS activity and that relative changes in PFC oxygenation contribute to these effects. Implications of these findings and directions for further research are discussed.